Norms and Coordination Tests for Badminton Players Aged 10-12 Years - Wiyanto, Agus; Rahayu, Tandiyo; Sulaiman,; Hidayah, Taufiq (International Journal of Psychosocial Rehabilitation, 2020)
Coordination is one aspect of physical condition that is very important in badminton. Badminton coordination tests can be identified through the appropriate test measurement tools and following the characteristics of badminton so that it can measure the ability of the badminton player as well as get a portfolio of badminton players who can be used as a guide for coaches and badminton. This study aims to produce norms and determine the coordination of badminton aged 10-12 years. The study involved 112 badminton respondents consisting of 80 male badminton players and 32 female badminton players through the recommendation of a badminton coach. The steps of the survey through a coordination test by doing a wall hit at a distance of 2 meters for 1 minute. Research findings on norms and coordination tests on badminton 10-12 years. This study concludes that badminton coaches/practitioners are advised to use coordination tests on badminton aged 10-12 years to determine the level of development of badminton in doing badminton.